2021
DOI: 10.31462/jseam.2021.01046056
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study on the development of the normal concrete-UHPC composite beam via wet casting

Abstract: Ultra-high-performance concrete (UHPC) is an innovative cementitious composite containing steel fiber reinforcement that can improve the behavior of structural elements thanks to its high strength and improved ductility properties. The mix design that provides these superior properties of UHPC also makes it a high-cost material. For this reason, the use of UHPC in parts where it contributes more significantly to the performance of the structural elements will lower down the costs and reduce the negative enviro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…since increasing the loading carrying capacity of the hybrid beam. Yalcinkaya [ 24 ] concluded that increasing the thickness of the UHPC layer from 15 mm to 30 mm in the tension zone led to the load–carrying capacity increment ratio of 20% and 34.6% respectively for the hybrid concrete (UHPC-NC) layered horizontally.…”
Section: Test Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…since increasing the loading carrying capacity of the hybrid beam. Yalcinkaya [ 24 ] concluded that increasing the thickness of the UHPC layer from 15 mm to 30 mm in the tension zone led to the load–carrying capacity increment ratio of 20% and 34.6% respectively for the hybrid concrete (UHPC-NC) layered horizontally.…”
Section: Test Results and Discussionmentioning
confidence: 99%
“…The arrangement of the layers and the thickness of the bottom layer affected the flexural strength of the hybrid concrete. Yalçınkaya [ 24 ] investigated the combination of the UHPC with a steel reinforcement with normal mortar (NM) and self–compacting mortar (SCM)which resulted in higher load carrying capacity. The interface of these hybrid concretes did not sustain any damage.…”
Section: Introductionmentioning
confidence: 99%
“…The tensile properties at the edge of the tensile zone of prestressed members are generally composed of two parts: the compressive stress caused by prestressing and the tensile strength of the concrete material [ 15 ]. The ultimate tensile strength of the UHPC structure at the edge of the tensile zone is calculated according to Equation (13).…”
Section: Theory and Calculationmentioning
confidence: 99%
“…In recent years, a considerable amount of experimental research has been undertaken on the flexural behavior of NC-UHPC composite beams, including that reported in [ 14 , 15 , 16 , 17 , 18 ]. In [ 14 ], the bond strength between UHPC and NC was found to be very high.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation